Foreword - Castelli, Stefano; Denessen, Eddie (International Journal about Parents in Education, 2023)
In the past decades, a large body of literature has been produced by researchers interested in the relationships between schools, teachers and parents (or families). This literature includes analyses and reflections on parental involvement from myriad research disciplines, theoretical and policy perspectives and research methodologies. However, closer scrutiny reveals that the label of “parental involvement” is an umbrella term, under which many different concepts and practices find a place. In this special issue we invited authors to delve more deeply into controversies and dilemmas that result from the variety of perspectives on parental involvement. Some examples of such controversies and dilemmas are: the use of parental involvement as a predictor of academic achievement in school effectiveness studies, parents’ rights and teachers’ stress, critiques on the neoliberal agenda that dictates effective parenting practices, inequality of access to diverse forms of parental resources, and the marginalizing effects of particular frameworks of parental involvement. The purpose of this special issue was aimed to provide a basis for future research and policies on family-school-partnership relations. We invited authors to formulate implications of their analyses and reflections for research, policy and practice. The title itself of the issue, a calque borrowed from "What We Talk About When We Talk About Love" by Raymond Carver, was an invitation towards a deeper understanding of the meaning of “parental involvement”. Topics discussed in this special issue are: teachers’ students’ and parents’ perspectives, teacher education, teacher students, teachers’ beliefs; homework, all day school, trust, parental engagement; comparative studies in education, also for what concerns National educational policies and diverse ethnic and linguistic families; emotional work, frontstage and backstage, stigma. Have a good read